Blood Group A Antigen Is a Coreceptor in Plasmodium falciparum Rosetting - Barragan, Antonio (American Society for Microbiology, 2000)
The malaria parasite Plasmodium falciparum utilizes molecules present on the surface of uninfected red blood cells (RBC) for rosette formation, and a dependency on ABO antigens has been previously shown. In this study, the antirosetting effect of immune sera was related to the blood group of the infected human host. Sera from malaria-immune blood group A (or B) individuals were less prone to disrupt rosettes from clinical isolates of blood group A (or B) patients than to disrupt rosettes from isolates of blood group O patients. All fresh clinical isolates and laboratory strains exhibited distinct ABO blood group preferences, indicating that utilization of blood group antigens is a general feature of P. falciparum rosetting. Soluble A antigen strongly inhibited rosette formation when the parasite was cultivated in A RBC, while inhibition by glycosaminoglycans decreased. Furthermore, a soluble A antigen conjugate bound to the cell surface of parasitized RBC. Selective enzymatic digestion of blood group A antigen from the uninfected RBC surfaces totally abolished the preference of the parasite to form rosettes with these RBC, but rosettes could still form. Altogether, present data suggest an important role for A and B antigens as coreceptors in P. falciparum rosetting.